A First‐Principles and Experimental Investigation of Nickel Solubility into the P2 NaxCoO2 Sodium‐Ion Cathode. Issue 26 (2nd August 2018) - Bianchini, Matteo; Wang, Jingyang; Clément, Raphaële; Ceder, Gerbrand
Abstract: The difficulty in finding positive electrode materials for sodium‐ion (Na‐ion) batteries with a large specific energy has slowed down their commercialization. Layered transition metal (M) oxides Na x MO2 with a two‐layer oxygen stacking (P2, 0.6 ≤ x ≤ 0.75), are promising candidates. However, the high average metal oxidation state needed during synthesis means that P2 Na x MO2 cathodes often require the introduction of high‐valent cations (Mn 4+, Ti 4+, Sn 5+, or Te 6+ ), limiting the cathode's performance. Using a combination of first‐principles calculations and experiments, the feasibility of P2 cathodes containing only electrochemically active nickel and cobalt cations is investigated. It is found that P2 Na x Ni y Co1– y O2 materials with x = 0.66, 0.75, and 0 ≤ y ≤ 0.33 are either thermodynamically stable or metastable yet close to the convex hull at typical P2 synthesis temperatures (≈1000 K). It is demonstrated that a novel P2 compound with y = 0.22 and both Ni 3+/4+ and Co 3+/4+ can be successfully synthesized. It is studied electrochemically and structurally, using in situ and ex situ X‐ray diffraction. It is demonstrated that the chemical space of P2 layered compounds is not fully explored yet and that ab initio phase diagrams allow the determination of new high‐specific energy positive electrodes to be targeted experimentally. Abstract : The exploration of the Na–Ni–Co–O phase diagram by first‐principles methods leads to the discovery of new P2 Na‐ion cathodes with unique cation valences and good performance. Detailed structural and electrochemical characterizations are provided to rationalize the material's limitations in terms of capacity.